An Advancements In Treatment Of Amyotrophic Lateral Sclerosis (ALS) - Weronika Ożóg; Martyna Borowska-Łygan; Patrycja Grzech; Lena Kreczyńska; Aleksandra Banach; Weronika Zubrzycka; Klaudia Piskorowska; Patryk Harnicki (Journal of Education, Health and Sport)
Introduction and Objective: Amyotrophic lateral sclerosis (ALS) is a devastating neurodegenerative disease characterized by the loss of motor neurons. Each year, amyotrophic lateral sclerosis is diagnosed in 4-5 people per 100,000 population.  The disease is commonly known as Lou-Gehrig's disease after the famous American baseball player who died two years after receiving the diagnosis at the age of 39.  The etiology of the disease is not fully understood, but gene mutations that contribute to the development of ALS have been identified.  Such mutations include the gene encoding superoxide dismutase type 1 (SOD1), C9orf72, TBK1 and FUS125, among others.  Since the first SOD1 mutation was identified as the genetic cause of SLA, there has been a significant milestone in clinical research aimed at finding a cure for this terminal and dreaded disease. In this article, we will discuss the early symptoms of ALS, factors that increase the risk of developing the disease and, most important, the knowledge and latest treatments, such as the use of antisense oligonucleotides (ASOs).